2011
DOI: 10.4028/www.scientific.net/amr.346.477
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on Aerodynamic Characteristics of Heavy-Duty Commercial Vehicle

Abstract: With the development of automotive technology and high-speed highway construction, the speed of the vehicles increase which cause the significant increase in the aerodynamic drag when road vehicles are moving. Thereby the power of the vehicles, fuel economy, operational stability and other properties are affected very seriously. Heavy-duty commercial vehicles as the most efficient way to transport goods on the highway are widely used, and the speed of the vehicles increases faster. Especially the demands for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Moreover, heavy commercial vehicles are massive and have high fuel consumption and long mileage; the demand for energy saving and emission reduction is more urgent. 4 Therefore, the successful application of a power-split system in heavy commercial vehicles is an important way and breakthrough to achieve energy saving and emission reduction of hybrid electric vehicles in China.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, heavy commercial vehicles are massive and have high fuel consumption and long mileage; the demand for energy saving and emission reduction is more urgent. 4 Therefore, the successful application of a power-split system in heavy commercial vehicles is an important way and breakthrough to achieve energy saving and emission reduction of hybrid electric vehicles in China.…”
Section: Introductionmentioning
confidence: 99%
“…Even a small amount of drag reduction can also reduce the cost of fuel consumption largely [3]. Therefore, it has got more and more people's extensive attention in recent years, and many scholars both at home and abroad do research about it [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…With China's rapid economic development, the development of highway provides great opportunities for the truck industries. Studies have shown that the high economic level and the long highway mileage will bring advantage to truck industry in both transport efficiency and fuel economy [1]. However, as the international oil reserves keep decreasing and the price of oil continue growing; the transportation costs have doubtlessly risen, which in turn bring great pressure to motor transportation.…”
Section: Introductionmentioning
confidence: 99%